Forensic botany : principles and applications to criminal casework - Coyle, Heather Miller (CRC Press, 2024)
"Forensic Botany: Principles and Applications to Criminal Casework, Second Edition updates what, at the time, was the very first book published on the subject. This latest edition offers a concise introduction to plant identification and biology, genetics and how to utilize and apply botanical evidence in criminal cases. In recent years, forensic botany, and the use of various plant and plant-derived evidence, has been increasingly utilized in criminal investigations and court cases. Likewise, forensic palynology and other such terms have entered the vernacular as botanical sciences have widened the applications in which such evidence can help solve cases. This includes the use of current and emergent genetic markers and DNA technology, toxicology, diatoms and pollen. The numerous advances since the last edition have published necessitated added coverage of the technology and testing capabilities that have achieved new levels as the field has developed. The book is comprised of various chapters written by contributing authors who are some of the top experts in the field. All chapters in the Second Edition are fully updated with several new chapters focusing on Random Amplified Polymorphic DNA (RAPD), Restriction Fragment Length Polymorphism (RFLP), and Amplified Fragment Length Polymorphism (AFLP), plant-derived toxins and forensic toxicology, identifying ancient plants used in burial practices for dating sites, digested plants as evidence, and more. Forensic Botany, Second Edition will provide scientists working with DNA, trace evidence, and botanical evidence-as well as investigators and legal professionals-with a thorough understanding of the latest advances, and current capabilities, in utilizing such evidence in investigating and adjudicating criminal cases"--